Analysis of Vegetation Dynamics of Tree Species inside the Forest of Institute of Forestry, Hetauda - Poudel, Animesh; Joshi, Mohit; Jha, Sweta; Bhatta, Sushila; Bidari, Anisha (Forestry: Journal of Institute of Forestry, Nepal, 2022)
A vegetation analysis of tree species was undertaken in the 92.69 hectares (ha) of the forest connected to the Institute of Forestry (IOF), Hetauda Campus. The study separated the forest into two strata, and a total of 10 circular sample plots (each plot measuring 500 m2) were constructed using systematic sampling with a sampling intensity of 0.5%. Enumeration of tree species was carried out within the sample plots. A total of 139 individual trees representing 16 (10 in stratum 1 and 12 in stratum 2) different tree species were recorded (60 in stratum 1 and 79 in stratum 2). Diversity indices were used for calculating vegetation parameters. According to the Importance Value Index, Shorea robusta was dominant in both strata, followed by other heterogenous species. The Shannon Wiener’s index and Simpson’s Diversity Index were higher in stratum 2, but the dominance index was lower than in stratum 1. Stratum 2 had a marginally higher measure of both evenness and richness than stratum 1. The study investigated the vegetation structure of the riverine and tropical moist deciduous forest in the study area. Increasing human interference had no significant effect on diversity and number of species among the strata. This study provides the baseline data necessary to characterize the phytodiversity of the forest area of the Institute of Forestry, Hetauda Campus for conservation and sustainable management.